2022
DOI: 10.1101/2022.09.05.22279602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent somatic symptoms are key to individual illness perception at one year after COVID-19

Abstract: Background: Sequelae of Coronavirus disease 2019 (COVID-19) were investigated by both patient-initiated and academic initiatives. Patient's subjective illness perceptions might differ from physician's clinical assessment results. Herein, we explored factors influencing patient's perception during COVID-19 recovery. Methods: Participants of the prospective observation CovILD study with persistent somatic symptoms or cardiopulmonary findings at the clinical follow-up one year after COVID-19 were analyzed (n = 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Symptom trajectories were also highly congruent with illness perception when adjusting for age, sex, initial COVID-19 severity and timing of infection. These findings are in line with a previous longitudinal study that found higher B-IPQ scores at 1 year after COVID-19 among individuals with a greater number of long COVID symptoms, reduced physical performance and higher fatigue score 21. Whilst we cannot proclaim a causal relationship, this association observed has two important implications.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Symptom trajectories were also highly congruent with illness perception when adjusting for age, sex, initial COVID-19 severity and timing of infection. These findings are in line with a previous longitudinal study that found higher B-IPQ scores at 1 year after COVID-19 among individuals with a greater number of long COVID symptoms, reduced physical performance and higher fatigue score 21. Whilst we cannot proclaim a causal relationship, this association observed has two important implications.…”
supporting
confidence: 91%
“…These findings are in line with a previous longitudinal study that found higher B‐IPQ scores at 1 year after COVID‐19 among individuals with a greater number of long COVID symptoms, reduced physical performance and higher fatigue score. 21 Whilst we cannot proclaim a causal relationship, this association observed has two important implications. Firstly, in clinical practice, our findings imply that the B‐IPQ—a rapid assessment tool—could be used to quantify long COVID severity in real‐time, monitor individuals' progression over time or screen individuals for risk of developing more severe long COVID, as suggested by the association between the M1 B‐IPQ and belonging to a 24‐month trajectory with a greater number of symptoms.…”
Section: Discussionmentioning
confidence: 97%